Coaching and Mentoring : A Critical Text - Western, Simon (New Delhi : SAGE Publications Ltd, 2012)
Coaching is often discussed as if it is a new 'profession' without adequate attention to how it has evolved, what underpins its practice or its training methods. Situating coaching in a wider social and historical context, Coaching and Mentoring that contemporary 'coaching theory' is more a collection of models and approaches mostly transferred from psychotherapy theory. Coaching claims to liberate creativity but can also entrap us by individualizing social experience. This vital new book brings a fresh and critical perspective on coaching and mentoring, challenging its normative assumptions and narratives, and proposing an ethical and emancipatory approach that takes it beyond instrumentalism and individualism.